Colchicine as a therapeutic drug in the management of oral submucous fibrosis - A randomized clinical study - Somisetty V M. Mounika; Rakesh K Manne; Natarajan Kannan; Swapna S Beeraka; Prathi V Sarath; Kanamarlapudi V Saikiran (Wolters Kluwer Medknow Publications, 2021)
Aim: The present study was planned to clinically determine the effectiveness of colchicine as a monotherapy in oral submucous fibrosis (OSMF) patients. Materials and Methods: Thirty OSMF patients were enrolled in the study and randomly divided into two groups by permuted-block randomization. Group A: Patients were treated with 0.5 mg colchicine (Goutnil) tablets twice daily for 3 months. Whereas, in Group B, intralesional injection of dexamethasone 2 mL, hyaluronidase 1,500 IU with 2 mL lignocaine HCl biweekly for 4-6 weeks were given. For all the individuals, baseline parameters like mouth opening, buccal mucosal flexibility, burning sensation, and tongue protrusion were recorded and reassessment was done at 1, 3, and 6 months followed by statistical analysis. Results: A significant decrease in the Visual Analogue Scale (VAS) score for severity of burning sensation was observed in Group A whereas mouth opening and tongue protrusion were higher in Group B patients. Statistically significant differences in the buccal mucosal flexibility were appreciable in the intragroup comparisons of both the groups from baseline to 6-month follow-up. Conclusion : Colchicine can be suggested as an adjuvant drug for reducing the burning sensation for the OSMF patients in whom steroids are contraindicated.